An azobenzene-modified redox-active ionic liquid electrolyte for supercapacitors. Issue 82 (27th September 2022) - Zhao, Yuhua; Chen, Yujuan; Zhuo, Kelei; Du, Quanzhou; Sun, Dong; Li, Zhiyong; Wang, Huiyong; Yan, Changling; Wang, Jianji
Abstract : An azobenzene-modified redox-active ionic liquid (IL) is demonstrated. It is incorporated into another IL to form a mixed electrolyte, which markedly improves the capacitance performance of supercapacitors via extra pseudocapacitance contribution. Abstract : A new redox-active ionic liquid (2-(4-(phenyldiazenyl)phenoxy)ethyl)-1-methyl-imidazolium tetrafluoroborate ([ABEMIM][BF4 ]) is demonstrated. It is incorporated into another ionic liquid ([EMIM][BF4 ]) to form a mixed IL electrolyte, which can markedly improve the capacitance performance of carbon-based supercapacitors via extra pseudocapacitance contribution. It opens up a new path to develop high-energy supercapacitors through introducing a redox-active ionic liquid to electrolytes.